Genome-Wide Genetic Variant Studies and Functional Insights into Downy Mildew Resistance in Rajasthan Maize Germplasm: A Review - Sharma, Ashwini; Tiwari, Yogita; Sharma, Kritika; Meena, Suyash; Bagchi, Preenon (Asian Journal of Biological and Life Sciences, 2026)
Maize production in India, particularly in Rajasthan and other tropical regions, faces significant challenges from downy mildew diseases, which cause substantial yield losses annually. Rajasthan maize germplasm represents a valuable genetic resource adapted to semi-arid conditions and harbors unique resistance alleles shaped by local selection pressures. Recent advances in genotyping-by-sequencing technology have revolutionized our ability to discover genome-wide single nucleotide polymorphisms and identify quantitative trait loci associated with disease resistance. This review synthesizes current knowledge on downy mildew resistance in maize, focusing on the genetic architecture of resistance, molecular markers for breeding applications, and functional characterization of candidate resistance genes. We examine the application of high-throughput sequencing technologies for SNP (Single Nucleotide Polymorphism) discovery, discuss major QTL (Quantitative Trait Locus) regions identified across different chromosomes, and analyze putative candidate genes including leucine-rich repeat receptors, kinases, and other defense-related proteins. The integration of genomic tools with traditional breeding approaches offers promising strategies for developing durable resistance in maize cultivars adapted to the Rajasthan agro-ecological zone. Understanding the genetic basis of downy mildew resistance in locally adapted germplasm is essential for sustainable maize production and food security in semi-arid regions. This article is a literature-based review and does not present new experimental data.
Keywords: Maize; Downy mildew; Genotyping-by-sequencing; Molecular markers; QTL mapping; Resistance genes; Rajasthan germplasm; Functional genomics